DEEP CIVIC LEARNING BERBASIS PENGALAMAN HARIAN: STUDI KASUS - Prasetiyo, Dwi Agung; Yuliastuti, Erlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study tries to describe Deep Civic Learning based on daily experience in internalizing Pancasila values for primary school children. The research was carried out at SD Islam As Salam, Bendo, Magetan Regency, in September 2025. A qualitative technique was used with a case study design. In-depth interviews with the principal, classroom teachers, Pancasila Education instructors, students, and parents, as well as document analysis, were used to gather data. Data were examined using data condensation, data display, conclusion drafting and verification. The results suggest that Deep Civic Learning is not merely enacted through conceptual explanation in the classroom, but mainly through daily experiences such as morning greetings, collective prayer, queuing, classroom duties, small-group deliberation, sharing learning tools, maintaining cleanliness, and resolving simple conflicts. The main findings reveal that daily experiences become concrete entry points for internalizing Pancasila values, teachers translate abstract civic values into simple actions, school routines establish a cycle of knowing, feeling, acting, and reflecting on values, and the success of Deep Civic Learning is shaped by teacher role modeling, school culture, and family support. This study proposes a conceptual model of Daily Experience-Based Deep Civic Learning as a humanistic and contextual alternative for Pancasila Education in elementary schools.